Pengaruh Intellectual Capital dan Literasi Keuangan terhadap Kinerja Bisnis UKM Ekonomi Kreatif - Iqbatullah, Danil; Nurkholis (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
SMEs are currently growing and competing in the transition from conventional business to knowledge-based business. Knowledge-based businesses must encourage SMEs to create competitive value to improve SME performance. This study aims to examine the effect of intellectual capital and financial literacy on the performance of SMEs. Resource Based Theory is used as the theoretical basis for investigating the performance of SMEs as an illustration of how to manage intangible assets. Data were collected through questionnaire survey techniques and then processed using SPSS. This study found customer capital and financial literacy can improve business performance. Human capital and structural capital as they lack awareness and development of investment in human capital and structural capital by SMEs. SMEs can maximize good relations with customers and increase financial literacy to improve business performance. It is therefore important that SMEs consider customer capital and the level of financial literacy in managing their SMEs to increase performance, market share, and expand networks.